2005
DOI: 10.3200/aeoh.60.1.7-15
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Blood Trihalomethane Concentrations Resulting From Differences in Water Quality and Water Use Activities

Abstract: Water disinfection is extremely important for the protection of public health; however, it also forms by-products, including trihalomethanes (THMs). Previous studies of health effects from disinfection by-products have lacked accurate methods to quantify exposure over time. As a first step in establishing a better system for exposure assessment, the authors investigated which household water use activities cause a significant increase in internal dose concentrations of THMs. In this study, 7 subjects in 2 diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 2 publications
0
33
1
3
Order By: Relevance
“…Its deficiency caused a reduction in photosynthesis; blackening of tubers in the case of potato and tips or margin of lower leaves of legumes, cotton, maize, and tobacco; and either scorching or burning of all small grains (Ashley et al 2005). Potassium plays a significant role in the maintenance of cellular organizations for regulating permeability of cell membranes and also keeping the protoplasm in a proper degree of hydration.…”
Section: Potassium and Its Importancementioning
confidence: 99%
“…Its deficiency caused a reduction in photosynthesis; blackening of tubers in the case of potato and tips or margin of lower leaves of legumes, cotton, maize, and tobacco; and either scorching or burning of all small grains (Ashley et al 2005). Potassium plays a significant role in the maintenance of cellular organizations for regulating permeability of cell membranes and also keeping the protoplasm in a proper degree of hydration.…”
Section: Potassium and Its Importancementioning
confidence: 99%
“…Pharmacokinetics differs among exposure routes [37]. Experimental studies in volunteers have shown a larger internal dose and longer duration in the bloodstream from activities involving inhalation and dermal absorption compared to ingestion [36,37]. As such, a proper exposure assessment should include ingestion and noningestion activities involving water contact in order to ascertain the relevant exposure window (Table 1).…”
Section: Exposure Assessment In Human Epidemiological Studiesmentioning
confidence: 99%
“…Trihalomethanes have been used in epidemiological studies as surrogates of total DBP content, although correlations among specific DBPs are variable [35]. Given that THMs (as well as other DBPs) are volatile and skin permeable, the exposure pathways are numerous, and include ingestion of water, inhalation and skin absorption while showering, bathing, swimming in treated pools, and hand dish-washing [36]. Pharmacokinetics differs among exposure routes [37].…”
Section: Exposure Assessment In Human Epidemiological Studiesmentioning
confidence: 99%
“…THMs, HAAs, and haloketones have been measured in human blood, urine, or exhaled breath after showering, bathing, or swimming [131,133,135,136,142,143,146,149]. Inhalation can sometimes give much higher exposure to volatile chemicals.…”
Section: Human Exposure To Cecs and Dbpsmentioning
confidence: 99%
“…Inhalation and dermal exposure to DBPs and CECs can occur during showering, bathing, and swimming in chlorinated swimming pools [131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148]. THMs, HAAs, and haloketones have been measured in human blood, urine, or exhaled breath after showering, bathing, or swimming [131,133,135,136,142,143,146,149].…”
Section: Human Exposure To Cecs and Dbpsmentioning
confidence: 99%